Effects of Rapid Palatal Expansion on the Upper Airway Space in Children with Obstructive Sleep Apnea (OSA): A Case-Control Study - Angela Galeotti; Roberto Gatto; Silvia Caruso; Simone Piga; Wanda Maldonato; Emanuela Sitzia; Valeria Viarani; Gaia Bompiani; Francesco Aristei; Giuseppe Marzo; Paola Festa (Children, 2023)
Obstructive Sleep Apnea (OSA) in children needs a multidisciplinary approach. Even if the first-line treatment of pediatric OSA is adenotonsillectomy, nowadays rapid palatal expansion (RPE) is considered a valid additional treatment. The aim of this study is to evaluate cephalometric changes in upper airways dimensions after rapid palatal expansion (RPE) in children suffering from Obstructive Sleep Apnea (OSA). A total of 37 children (range age 4–10 years) with diagnosis of OSA referred to Dentistry Unit of Bambino Gesù Children’s Research Hospital IRCCS (Rome, Italy) were included in this pre-post study and underwent lateral radiographs at the start (T0) and at the end (T1) of a RPE treatment. Inclusion criteria were: diagnosis of OSA confirmed by cardiorespiratory polygraphy (AHI > 1) or pulse oximetry (McGill = >2), skeletal maxillary contraction evaluated by presence of posterior crossbite. A control group of 39 untreated patients (range age 4–11 years), in good general health, was set up. A paired T-test was used to investigate the statistical differences between T0 and T1 values in both groups. The results showed a statistically significant increase of nasopharyngeal width in the treated group after RPE treatment. Moreover, the angle that identifies mandibular divergence compared to palatal plane (PP-MP°) was significantly reduced. In the control group, no statistically significant differences were observed. The present study showed that RPE treatment determines a significant sagittal space increase in the upper airways space and a counterclockwise mandibular growth in children with OSA compared to a control group. These results suggest that a widening of the nasal cavities induced by RPE may support a return to physiological nasal breathing and promote a counterclockwise mandibular growth in children. This evidence confirms the crucial role of the orthodontist in the management of OSA in pediatric patients.